Clinical features of non-compaction cardiomyopathy across age groups: a retrospective study of 415 patients - Ying Li; Jimei Chen; Min Qiu; Miao Tian; Ziqin Zhou; Ruyue Zhang; Jiazichao Tu; Linjiang Han; Shuheng Zhou; Xinming Li; Jian Zhuang; Shusheng Wen (Open Heart)
Background Non-compaction cardiomyopathy (NCM) is a rare inherited cardiac disorder associated with adverse cardiovascular outcomes, including heart failure, arrhythmias and sudden cardiac death. Currently, the clinical manifestations of NCM lack comprehensive characterisation across different age groups in large-scale studies. This investigation aims to systematically analyse the clinical characteristics of patients with NCM across various age demographics.Methods A retrospective analysis was conducted on 415 patients with NCM treated at the Guangdong Institute of Cardiovascular Disease from January 2013 to January 2023. We comprehensively collected and analysed clinical data, including presenting symptoms, arrhythmia patterns, echocardiographic parameters and cardiac magnetic resonance imaging findings.Results The study cohort (n=415) was stratified into three age groups: infants (0–1 year, n=169), children/adolescents (1–18 years, n=149) and adults (>18 years, n=97). Heart failure was the predominant clinical manifestation across the entire cohort, affecting 112 patients (27%). Notably, heart failure was most prevalent in adult patients (54.6%, n=53), while cardiac murmur was the primary presenting symptom in both infant and child/adolescent groups (19.5%, n=33 and 17.4%, n=26, respectively). Across all age groups, patients with NCM with concurrent mitral regurgitation (MR) demonstrated significantly reduced left ventricular ejection fraction and fractional shortening compared with those without valvular disease (p<0.05). Additionally, left ventricular end-systolic diameter (LVESD) and end-diastolic diameter (LVEDD) were significantly increased in patients with MR (p<0.05). A significant correlation was observed between both LVESD and LVEDD measurements and MR area in patients with NCM (p<0.05).Conclusion Patients with NCM with concomitant MR consistently exhibited left ventricular dilatation and systolic dysfunction across all age groups. Significant age-related variations were observed in clinical presentations, arrhythmia patterns and the prevalence of congenital and valvular heart disease. Understanding these age-specific clinical characteristics is crucial for accurate diagnosis, optimal therapeutic management and future research directions in NCM.